Effect of polyunsaturated fatty acids intake on the occurrence of current asthma among children and adolescents exposed to tobacco smoke: NHANES 2007-2018 - Chunyan Wang; Li Wang; Wanling Ding; Feng Zhao; Guoqiang Hou (BMC, 2024)
Abstract Background Asthma is an airway inflammatory disease driven by multiple factors with a high incidence in children and adolescents. Environmental tobacco smoke exposure (TSE) and diet are inducing factors for asthma. The potential of omega-3 polyunsaturated fatty acids (PUFAs) to alleviate asthma symptoms by their anti-inflammatory effects has been explored. However, to date, no studies have explored the effect of dietary PUFAs intake on the asthma in children and adolescents exposed to tobacco smoke. Objective We aimed to examine the effect of dietary PUFAs intake on the current asthma in children and adolescents exposed to tobacco smoke. Methods Data of this cross-sectional were extracted from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. Children and adolescents with serum cotinine concentration ≥ 0.05 ng/mL were defined to exposed to tobacco smoke. Dietary PUFAs intake information were obtained from 24 h recall interview. The weighted univariate and multivariate were utilized to explore the effect of PUFAs on the association of asthma and TSE, with adjusted odds ratios (AORs) and 95% confidence intervals (CIs). These moderating effects were further explored based on the age, gender and body mass index (BMI) and sedentary time. Results Totally, 7981 eligible children and adolescents were included, with the mean age of 11.96 ± 0.06 years old. Of whom, 1.024 (12.83%) had current asthma. After adjusted all covariates, we found children and adolescents with TSE had high occurrence of current asthma (AOR = 1.2, 95% CI 1.03-1.63); We also found omega-3 PUFAs intake (P for interaction = 0.010), not omega-6 PUFAs (P for interaction = 0.546), has a moderating effect on the association of TSE and current asthma. Moreover, we further observed that children and adolescents with TSE and low omega-3 PUFAs intake had high occurrence of current asthma (AOR = 1.58, 95% CI 1.19-2.10), while no significant association was found in children and adolescents with high omega-3 PUFAs intake (all P > 0.05). This moderating effect was more prominent in children and adolescents aged ≤ 12 years old (AOR = 1.62, 95% CI 1.06-2.47), girls (AOR = 2.14, 95% CI 1.15-3.98), overweight (AOR = 1.87, 95% CI 1.01-3.47) and sedentary time > 6 h (AOR = 1.96, 95% CI 1.00-3.86). Conclusion We found dietary omega-3 PUFAs plays a moderating effect on the association of asthma and TSE in children and adolescents, especially in children and adolescents aged ≤ 12 years, girls, overweight or sedentary time > 6 h. This moderating effect suggested higher omega-3 intake has potential benefits in decreasing the occurrence of asthma in children and adolescents who exposed to tobacco smoke.